STIMULASI MATERNAL ROLE PADA IBU HAMIL DI WILAYAH PUSKESMAS BANDARHARJO SEMARANG - Sri Wahyuni; Tutik Rahayu; Moch Aspihan (LPPM Universitas Pekalongan, 2021)
Pregnancy is a part of a woman's physiological process that requires adaptation both physically and psychologically. At this stage, women will prepare themselves to achieve their role / maternal role. Maternal roles require support to facilitate the adaptation phase, especially in primigravidas. In addition to support, stimulation is also needed to increase maternal roles. The purpose of this community partnership program is to implement maternal role stimulation in pregnant women in the Bandarharjo village area. The PKM implementation method is carried out in 4 stages. The implementation of stimulation is carried out in 4 stages, namely socialization, competency improvement, skills training and monitoring evaluation. The results of PKM showed an increase in maternal roles in primigravida mothers after being given stimulation. An increase of 44.5%. Keywords: stimulation, maternal role, pregnant women